2021
DOI: 10.1111/bjh.17962
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the prevalence of mental health disorders among Black American adults with sickle cell disease compared to those with non‐heritable medical conditions or no medical conditions

Abstract: Our aim was to determine differences in the prevalence of mental health disorders between Black Americans living with sickle cell disease (SCD) and Black Americans with other, non-heritable medical conditions, or no medical conditions. We examined the prevalence of mental health disorders among a non-institutionalized, community sample of Black adults in the US from the National Survey of American Life. We compared the odds of mental health disorders between Black American adults with SCD and those with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The anxiety and depression rates in our sample were much higher than that among the general US population in 2019, who reported moderate/severe symptoms of anxiety (score GAD 7 ≥ 10) [43] at a rate of 7.1%, and depression (score PHQ 8 ≥ 10) at a rate of 7.0% [44]. It was also much higher than rates reported in a population of adults with SCD who participated in the National Survey of American Life survey which used structured diagnostic interviews and DSM-IV criteria and found that 24.7% of subjects had an anxiety disorder and 38.8% had a mood disorder [45]. Fatigue and pain can lead to anxiety and depressive disorders [46].…”
Section: Discussionmentioning
confidence: 99%
“…The anxiety and depression rates in our sample were much higher than that among the general US population in 2019, who reported moderate/severe symptoms of anxiety (score GAD 7 ≥ 10) [43] at a rate of 7.1%, and depression (score PHQ 8 ≥ 10) at a rate of 7.0% [44]. It was also much higher than rates reported in a population of adults with SCD who participated in the National Survey of American Life survey which used structured diagnostic interviews and DSM-IV criteria and found that 24.7% of subjects had an anxiety disorder and 38.8% had a mood disorder [45]. Fatigue and pain can lead to anxiety and depressive disorders [46].…”
Section: Discussionmentioning
confidence: 99%
“…One particularly vulnerable population is individuals with sickle cell disease (SCD), a heritable condition that affects millions of people worldwide and >100,000 people in the United States, most of whom are of African descent [ 5 ]. Among patients with SCD, 38.8% present with mental health disorders [ 6 ]. A review of the literature on mental health symptoms in SCD found that 22% to 57% of individuals with SCD report clinically significant depressive symptoms depression when screened [ 7 ].…”
Section: Introductionmentioning
confidence: 99%